A new switched reluctance motor with distributed winding. Issue 6 (28th October 2014) - Doležel, Ivo; Ma, Qingqing; Ge, Baoming; Bi, Daqiang; J.T.E. Ferreira, Fernando; T. de Almeida, Aníbal
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a new three-phase switched reluctance motor (SRM), and achieve high-torque and low-cost. This new SRM's winding configuration uses the double-layer distributed windings, which is different from the conventional SRM's single tooth coils. Design/methodology/approach – The operating principle of new SRM is analyzed, and the voltage equation and the generated torque are deduced. Finite element method (FEM) and finite element circuit coupled method are utilized to evaluate the new motor's operating performances. The two dimensional (2D) frequency response analysis model is employed in the FEM model. Based on the 2D frequency response analysis model, the magnetic field distribution, self-inductance, and mutual-inductance for the new SRM are analyzed in detail. A co-simulation model using FE analysis package and Matlab-Simulink is proposed to simulate the new SRM drive. The simulated and experimental results verify the new SRM. Findings – For the new SRM with double-layer distributed windings, a co-simulation method is proposed to analyze its characteristics. The new SRM presents lower torque ripple coefficient and generates larger torque than the conventional SRM, with three-wire and standard full bridge power converter, rather than six-wire and asymmetric half-bridge converter for conventional SRM. Originality/value – This paper proposes a new SRM with the double-layer distributed windings driven by a standard full bridge inverter. In order to calculate dynamic characteristics of the new SRM, a co-simulation method using FEM and Simulink is proposed to simulate the new SRM drive, where the power inverter and the current chopping control algorithm are implemented.